Family homeless shelters as contexts for early childhood development: Shelter resources and staff capacity. - Halverson, McKenna M.; Wallace, Laura E.; Tebepah, Tariere C.; Riccelli, Victoria; Bajada, Allison; Herbers, Janette E. (Child & Family Social Work, 2024)
Family homeless shelters are critical contexts in which many young children develop; however, little is known about the developmental appropriateness of these settings, including their resources and the capacity of their staff to effectively meet the needs of the children and families they serve. The current study involves both quantitative and qualitative components to assess aspects of developmental appropriateness of US shelter spaces for children ages birth to 5 years, with an emphasis on staff knowledge, parenting programmes, and play spaces. Participants were 64 staff working in different family homeless shelters representing all 10 Housing and Urban Development regions. Data were collected via semistructured phone interviews. Results indicated that most shelters offered some type of parenting programme (65.5%) and had some developmentally appropriate space for families with young children (87.5%); however, the nature of these spaces and programmes varied considerably, with very few respondents describing use of evidence‐based practices. Findings on knowledge of early child development among shelter staff indicated substantial need for trainings on a range of topics, including typical child development, parent–child relationships, and impacts of trauma on families with young children. Furthermore, we identified a need for better measurement tools to assess knowledge of child development.